Effect of COVID‐19 on Acute Ischemic Stroke Hospitalizations and Treatments: Population‐Level Experience. Issue 1 (3rd May 2022) - Kim, Youngran; Sharrief, Anjail; Khose, Swapnil; Abdelkhaleq, Rania; Salazar‐Marioni, Sergio; Krause, Trudy Millard; McCullough, Louise D.; Zhang, Guo‐Qiang; Sheth, Sunil A.
Abstract : Background: Several studies have reported changes in the volume and type of acute ischemic stroke (AIS) hospitalizations during the early stage of the COVID‐19 pandemic. However, population‐based assessments, which include lower volume centers and more comprehensive geographic areas, are limited. Here, we evaluate an entire state‐level experience during the first peak COVID pandemic and compare against a 1‐year prior historical period. Methods: We conducted a retrospective population‐based study using the Texas Inpatient Public Use Data File, capturing all discharges from hospitals in the State of Texas, except federal hospitals. AIS admission volumes, patient characteristics, proportions of large vessel occlusion (LVO), admission rates to comprehensive stroke centers, use of intravenous tissue plasminogen activator and endovascular treatment, and patient outcomes were compared between April 1, 2019 and June 30, 2019 (historical control period) and April 1, 2020 and June 30, 2020 (pandemic period). Results: A total of 9277 hospitalized AIS cases were identified during the pandemic period, a decrease of 12% (10 524) compared with the control period. Cases without LVO dropped by 15%, whereas LVO cases dropped by only 5%. There were no significant differences in age or race and ethnicity of patients. While admission rates to comprehensive stroke centers (39.6% versus 39.4%, P =0.81) and endovascular treatment use in LVO (17.0% versus 16.3%, P =0.45) were not different between the 2 periods, the use of intravenous tissue plasminogen activator (15.0% versus 13.6%, relative risk [RR], 0.90; 95% CI, 0.84–0.97; P =0.004) decreased. The percentage of patients who died or were discharged to hospice increased from 7.2% to 8.25% (RR, 1.17; 95% CI. 1.06–1.29; P =0.001). Conclusions: This study from a statewide population‐level analysis confirms smaller hospital‐based cohorts observing decreasing numbers of milder AIS admissions, and lower use of thrombolysis. Although LVO admissions and endovascular treatment use were largely unchanged, these findings suggest missed treatment opportunities for patients with AIS in the pandemic. Abstract :